'Cryo-immuno-therapy' is superior to intralesional Candida antigen monotherapy in the treatment of multiple common warts. (17th November 2021) - Attwa, Enayat; Elawady, Rehab; Salah, Eman
Abstract: Background: The treatment of multiple common warts can be challenging. Cryotherapy is commonly used for eradicating common warts with variable success. Intralesional Candida antigen has showed promising results in treating different human papillomavirus infections. Objectives: The aim of this study was to evaluate the safety and efficacy of combining cryotherapy with Candida antigen intralesional immunotherapy for the treatment of multiple common warts. Patients and methods: A total of 60 patients were randomly and equally assigined into three groups: Group Awho received intralesional Candida antigen monotherapy, Group Bwho was treated by cryotherapy alone, and Group Cwho was treated by a combination of cryotherapy with intralesional antigen immunotherapy or 'cryo-immuno-therapy.' The treatment sessions were done every 2 weeks to a maximum of five sessions. All patients were followed up for 3 months to detect possible relapses. Any adverse effects were recorded and patients' satisfaction was evaluated at the end of treatment. Results: The 'cryo-immuno-therapy' group resulted in (40%) complete clearance of lesions which was significantly superior to immunotherapy monotherapy clearance rate (20%). Conclusions: 'Cryo-immuno-therapy' is a new combination therapy for multiple common warts. This combination is easy to apply, safe, of low cost, and higher efficacy in contrast to the traditional intralesional Candida antigen monotherapy.